The immunological bases of alemtuzumab as induction-therapy in pediatric-onset multiple sclerosis - Puthenparampil, Marco; Gaggiola, Marta; Rinaldi, Francesca; Nosadini, M.; Sartori, S.; Perini, Paola; Gallo, Paolo (Frontiers in Immunology, 2025)
Pediatric-Onset Multiple Sclerosis (POMS) is characterized by both white and grey matter inflammation, as well as by a higher risk of long-term physical and cognitive disability. The peculiar immunopathogenic mechanisms of POMS suggests that the use of induction therapies, including alemtuzumab (ALTZ), might be a promising approach, at least for postpuberal (> 11 yo) POMS. Although no data on the use of induction therapies in POMS are available from clinical trials currently, case series or case reports on the effect of alemtuzumab (ALTZ) have been recently published. In this review we have briefly revised the immunopathogenic features of POMS, as well as on how ALTZ might impact on them, reporting its efficacy observed in different POMS cohorts.